Precision versus Protocol: A Cross-sectional Analysis of Gastric Biopsy Techniques in Detecting Premalignant Lesions - Mrunal Kesari; Yoganand Patil; V Kalaivanan; Indranil Bhattacharya (Journal of Clinical and Diagnostic Research)
Introduction: Patients with Chronic Atrophic Gastritis (CAG) and Gastric Intestinal Metaplasia (GIM) are at risk of developing gastric adenocarcinoma. The early and accurate detection of these lesions is critical for effective intervention and improved patient outcomes. Aim: To study the Sydney protocol and targeted single-site biopsy in detecting premalignant gastric lesions, identifying the most reliable method for early diagnosis. Materials and Methods: This was a cross-sectional study conducted in the Department of Pathology and Laboratory Medicine at Jagjivan Ram Hospital, Western Railway, Mumbai, Maharashtra, India from June 2023 to February 2024. A total of 100 gastric biopsies were included, comprising 50 cases of targeted single-site biopsy and 50 cases following the Sydney protocol. The Sydney protocol recommends obtaining biopsies from five specific sites in the stomach: two from the antrum, two from the body and one from the incisura angularis. The parameters studied were atrophy and intestinal metaplasia, which were assessed using histopathological evaluation of gastric biopsy specimens. The results were analysed by calculating interobserver agreement using kappa statistics to evaluate the reproducibility and reliability of the diagnostic criteria. Results: Out of 50 targeted single-site biopsies, urease was positive in 14 (28%) cases. A total of 14 (28%) patients had CAG, of which 12 were stage I and 2 were stage II. A total of 4 (8%) patients had intestinal metaplasia, out of which three were stage I and one was stage II. Out of 50 Sydney protocol-compliant biopsies, 20 (40%) patients’ urease tests were positive in at least one biopsy site. A total of 30 (60%) patients had CAG, of which 15 (30%) had CAG in all three sites (corpus, antrum and incisura), 4 (8%) had CAG only in the corpus, 4 (8%) had CAG only in the antrum, 3 (6%) had CAG in both the antrum and incisura, 2 (4%) had CAG in both the corpus and incisura, and 2 (4%) had CAG only in the corpus. Out of these 30 patients with CAG, 18 (36%) were classified as stage I, 9 (18%) as stage II, and 3 (6%) as stage III. A total of 10 (20%) patients had GIM, of which 6 (12%) had GIM only in the antrum, 2 (4%) had intestinal metaplasia in both the corpus and antrum, 1 (2%) had intestinal metaplasia in both the antrum and incisura and 1 (2%) had intestinal metaplasia only in the incisura. Out of these 10 patients with intestinal metaplasia, 5 (10%) were classified as stage I, 3 (6%) as stage II, 1 (2%) as stage III, and 1 (2%) as stage IV. Additionally, 3 (6%) patients had low-grade dysplasia. Conclusion: The Sydney protocol outperforms targeted single-site biopsy in detecting premalignant gastric lesions due to its comprehensive sampling from multiple sites, thereby reducing the risk of missed lesions. This thorough approach ensures accurate diagnosis and highlights the importance of endoscopic follow-up for ongoing patient management.